2005
DOI: 10.1111/j.1939-165x.2005.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum alkaline phosphatase activity with the healing process of long bone fractures in dogs

Abstract: Serial determination of serum ALP activity during fracture healing could be an additional tool in predicting fractures at risk of developing a nonunion, helping the clinician to choose the appropriate intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 14 publications
6
35
1
6
Order By: Relevance
“…In a study performed by Komnenou et al (2005) on dogs, and in one performed by Singh Ajai et al (2013) on human patients, the serum alkaline phosphatase (ALP) activity was determined throughout the healing process of long bone diaphyseal fractures. In both studies it was observed that serum ALP activity remained within the reference limits during the entire postoperative period in patients that had developed a non-union process, probably indicating a suppression of osteoblastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Komnenou et al (2005) on dogs, and in one performed by Singh Ajai et al (2013) on human patients, the serum alkaline phosphatase (ALP) activity was determined throughout the healing process of long bone diaphyseal fractures. In both studies it was observed that serum ALP activity remained within the reference limits during the entire postoperative period in patients that had developed a non-union process, probably indicating a suppression of osteoblastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…These markers are also used in several animal species in clinical and orthopaedic research, particularly in sheep (Newman et al 1995, Chavassieux et al 1997, Turner 2002, Taniguchi et al 2003, Klein et al 2004, Komnenou et al 2005, Seebeck et al 2005.…”
mentioning
confidence: 99%
“…Sheep have also been used as an experimental model in orthopaedic studies, with assessment of bone healing usually acquired by means of imaging, histological and histomorphometric techniques and mechanical tests . Nevertheless, measurements of serum markers of bone turnover could possibly also aid in the evaluation of cellular function in fracture or bone defect healing research, supplying information about the organic response to the lesion and to the selected treatment (Taniguchi et al 2003, Klein et al 2004, Komnenou et al 2005, Seebeck et al 2005.…”
mentioning
confidence: 99%
“…Sendo a fosfatase alcalina um indicador de atividade osteoblástica durante a reparação de fratura, o aumento dos níveis séricos concomitante á formação do calo ósseo sugerem deposição de matriz óssea (KOMNENOU et al, 2005), porém a grande variação dos valores entre os indivíduos remete a graus variados de atividade e pode diminuir a importância de tais resultados. Conforme Carano e Filvaroroff (2003) e Doblaré et al (2004), o calo ósseo encontra-se formado ao fi nal da segunda ou terceira semana e a partir deste período ocorre diminuição da atividade osteoblástica.…”
Section: Resultsunclassified